RESPON PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomea reptans poir) TERHADAP PEMBERIAN PUPUK KANDANG DAN BIOURINE SAPI - Modesta Yuliana Hartika; I Made Sukerta; Listihani; Bagus Putu Udiyana (Agrofarm: Jurnal Agroteknologi, 2023)
Kale plans is one type of horticultural plant that is easy to cultivz kale plants can grow optimally if they are planted on land that has high enough macro and micro nutrients and loose soil conditions, one of the macro nutrients needed by this vegetable is nitrogen nutrients, because nitrogen is a basic nutrient forming proteins, nucleic acids, and chlorophyll that are useful in the process of photosynthesis. This study aims to determine the "Response of Growth and Yield of kale plans (Ipomea reptans poir). Due to Dosage of Manure and Concentration of Cattle Biourine. The method used is a Randomized Block Design (RAK) with factorial treatment with 2 treatment factors. Factor 1: Dosage of cow manure with 5 levels, namely K0 (without cow manure), K1 (cow manure 30 gr/10 kg of soil), K2 (cow manure 60 gr/10 kg of soil), K3 (cow manure 90 g / 10 kg of soil), and K4 (cattle manure 120 g / 10 kg of soil). Factor 2: concentration of bovine biorin with 5 levels, namely B0 (without beef biorin), B1 (bovine biorin 80 ml/1 liter of water), B2 (bovine biorin 160 ml/1 liter of water), B3 (bovine biorin 240 ml/1 liter water), and B4 (beef biorin 320 ml/1 liter of water). The results showed that treatment (K4B4) with a dose of cow manure 120 g/10 kg of soil with a concentration of biourin 320 ml/1 liter of water gave the best growth compared to other treatments for all observation parameters such as plant height (cm), number of leaves (strands). , leaf area (cm²), total fresh weight (g), total oven dry weight (g), fresh weight without roots (g), and oven dry weight without roots (g). and the lowest was in the K0B0 treatment without a dose of manure and cow biourin concentration.